The Classification of Households with Respect to the "Family 500+" Benefit - Agnieszka Samsel (Communications of International Proceedings, 2020)
Pro-family policy in Poland has changed since April 2016. The programme described as "Family 500+" has been introduced and it has provided financial support for Polish households. A household, taking advantage of the programme, may treat it as an additional financial support (apart from remuneration for work performed) or the main source of income. The purpose of this article is to explain the concept of a household from an economic point of view, as well as to indicate the differences between related concepts. Additionally, the work aims at characterizing the pro-family policy of Poland (also over the years). The main purpose is the division of households (classification) on the basis of the financial use of the funds from the "Family 500+" benefit. The research methods used in the article include: critical analysis of literature, examination of documents, a questionnaire and statistical analysis.
Keywords: Households; Pro-Family Policy; "Family 500+”; Household Finances.